Time Savings and Surgery Task Load Reduction in Open Intraperitoneal Onlay Mesh Fixation Procedure - Sanjoy Roy; Jeffrey Hammond; Jessica Panish; Pullen Shnoda; Sandy Savidge; Mark Wilson (The Scientific World Journal)
Background. This study assessed the reduction in surgeon stress associated with savings in procedure time for mechanical fixation of an intraperitoneal onlay mesh (IPOM) compared to a traditional suture fixation in open ventral hernia repair. Study Design. Nine general surgeons performed 36 open IPOM fixation procedures in porcine model. Each surgeon conducted two mechanical (using ETHICON SECURESTRAPTM Open) and two suture fixation procedures. Fixation time was measured using a stopwatch, and related surgeon stress was assessed using the validated SURG-TLX questionnaire. T-tests were used to compare between-group differences, and a two-sided 95% confidence interval for the difference in stress levels was established using nonparametric methodology. Results. The mechanical fixation group demonstrated an 89.1% mean reduction in fixation time, as compared to the suture group (p<0.00001). Surgeon stress scores measured using SURG-TLX were 55.5% lower in the mechanical compared to the suture fixation group (p<0.001). Scores in five of the six sources of stress were significantly lower for mechanical fixation. Conclusions. Mechanical fixation with ETHICON SECURESTRAPTM Open demonstrated a significant reduction in fixation time and surgeon stress, which may translate into improved operating efficiency, improved performance, improved surgeon quality of life, and reduced overall costs of the procedure.